Heavy metal concentration in wet market ginger and its assessment on public health risks - Shimi, G A; Hossain, M K; Islam, R; Tasnova, A R; Mondol, M N; Chamon, A S (Bangladesh Journal of Scientific and Industrial Research, 2024)
Heavy metals like Cr, Cu, Pb, and Zn can induce public health risks through consumption over time. Gingers of both native and foreign origin were randomly collected from two large wet markets, Karwanbazar and Shyambazar, Dhaka, Bangladesh and were analyzed to determine the concentrations of heavy metals using atomic absorption spectroscopy. The data were used to assess various health risk indices. From the results, it is observed that the Pb concentration of almost all the ginger samples was higher than the MPL and consumption of such samples can be considered hazardous. But the concentration of Cu and Zn in all of the ginger samples was found to be lower than the MPL. The ADI of Cr, Cu, Pb, and Zn in native ginger samples were all below the PMDTI. Moreover, HI of half of the imported ginger samples was above unity and therefore injurious to human health when consumed. Bangladesh J. Sci. Ind. Res. 59(3), 169-178, 2024